Water-soluble turmeric with low hygroscopicity and high stability as well as preparation method and application thereof
By preparing cross-linked chitosan and curcumin nanoparticles, combined with specific wall materials and processing techniques, the problem of curcumin absorbing moisture and clumping under high temperature and humidity conditions was solved, thereby improving water solubility and stability, making it suitable for the food, pharmaceutical and cosmetic fields.
Patent Information
- Application Number
- CN202511929173.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-01-23
AI Technical Summary
Existing technologies cannot maintain the water solubility and stability of curcumin in high temperature and high humidity environments, causing the product to absorb moisture and clump during long-distance sea transport, which affects its application and promotion.
Water-soluble turmeric with low hygroscopicity and high stability was prepared by using cross-linked composite nanoparticles of chitosan and curcumin, combined with wall materials such as sodium octenyl succinate starch, maltodextrin, highly branched cyclic dextrin and hydroxypropyl starch, through emulsification, homogenization and wet grinding, and finally spray drying.
The prepared water-soluble turmeric maintains good fluidity and stability under high temperature and high humidity conditions, meeting the transportation requirements of international trade. The product has a high curcumin content and is suitable for the food, pharmaceutical and cosmetic fields.
Smart Images

Figure CN121370830A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of natural product deep processing, and in particular to a low-hygroscopicity and high-stability water-soluble curcuma and a preparation method and application thereof. BACKGROUND
[0002] Curcuma is extracted from the rhizome of Curcuma aromatica Salisb, Curcuma longa L. or Curcuma zedoaria (Berg.) Rosc., and also exists in Acorus calamus L. of Araceae. The main active ingredients include curcumin, demethoxycurcumin and bisdemethoxycurcumin, among which curcumin has the highest content. Curcumin is not soluble in water, but is easily soluble in ethanol, glacial acetic acid and propylene glycol, has good thermal stability, but is sensitive to light and is easily degraded and faded under light conditions.
[0003] As a natural colorant, curcumin has strong coloring ability and has been widely used in the food industry worldwide, and can be added as a natural pigment or used for coloring food raw materials. At the same time, curcumin is also a traditional Chinese medicine, which was first recorded in Tang Bencao, and has the effect of “breaking blood, promoting qi, and relieving pain”. In India, it is a commonly used medicine of Ayurveda medicine; in Japan, it is used as a functional food raw material; in Europe and the United States, it is commonly used as a dietary supplement; the National Cancer Institute of the United States has listed it as the third generation of chemical anticancer agents, and it was included in the United States Pharmacopoeia in 2000, and was recognized as a dietary nutrient supplement by the U.S. FDA in 2016. Modern research has confirmed that curcumin has anti-inflammatory, antioxidant, free radical scavenging, tumor inhibition and cardiovascular protection and other pharmacological effects, and shows good potential for preventing and treating various inflammations and diseases.
[0004] Curcumin has poor water solubility and low stability, and often needs to be modified to improve its applicability in actual application, so as to solve its deficiencies and shortcomings in terminal application. In international trade, it often needs to go through a long sea transportation, and the high temperature and high humidity environment at sea is easy to make the water-soluble curcuma powder absorb moisture and caking, thereby causing the quality to decrease and restricting its popularization and application. Therefore, it has become an urgent key technical subject in the current industry to develop a curcumin powder product with strong water solubility, high stability, good fluidity and not easy to absorb moisture and caking in harsh environment, so as to meet the requirements of long-distance sea transportation.
[0005] At present, researchers have carried out more researches on improving the solubility, stability and absorption effect of curcumin to adapt to different demand scenarios, which mainly focus on terminal application. CN120242972A uses the cross-linked network of chitosan and gelatin as a sustained-release carrier for curcumin, and prepares curcumin into an oil-in-water emulsion which is then loaded on aerogel. After absorbing water, the aerogel is easier to release. The prepared curcumin-containing adsorbent has excellent hygroscopicity. Sun Yingqian et al. (Sun Yingqian, Wan Shuxin, Sun Li, et al. Preparation of curcumin chitosan microspheres and study on their release in vitro and in vivo [J]. Modern Biomedicine Progress, 2012, 12(29):7. DOI: CNKI: SUN: SWCX.0.2012-29-015.) use acetic acid solution of chitosan as raw material, dissolve curcumin in diethylene glycol ether, use trisodium phosphate for charge neutralization and precipitation, centrifuge to collect the precipitate, and freeze-dry to prepare curcumin chitosan microspheres. The curcumin chitosan microspheres prepared by this method have a certain sustained-release effect, but the water solubility of the product is poor, and diethylene glycol ether as a solvent has high biological toxicity, which cannot meet the safety requirements for use in food. Li Na et al. (Li Na, Tang Dandan, Wang Liwen, et al. Preparation and characterization of curcumin phospholipid complex chitosan microsphere dry powder inhalation by spray drying [J]. Chinese Herbal Drugs, 2014, 45(17):7. DOI: 10.7501 / j.issn.0253-2670.2014.17.010.) first prepare curcumin phospholipid complex, then mix it with chitosan acetic acid solution, use trisodium phosphate for charge neutralization and precipitation, and then spray dry to prepare curcumin phospholipid complex chitosan microspheres. The product has poor flowability, and the change of phospholipid content has a great influence on the hygroscopicity and flowability of the product, which also cannot meet the requirements of low hygroscopicity and powder flowability of the product in high temperature and high humidity environment. CN117752615A discloses a kind of curcumin-loaded chitosan- lecithin nanoparticles and a preparation method thereof. The nanoparticles are prepared by dissolving curcumin and lecithin in hot tetrahydrofuran-dichloromethane, then mixed with chitosan acetic acid solution and freeze-dried. The prepared curcumin-loaded chitosan- lecithin nanoparticles have good thermal stability and water solubility. The above-mentioned documents all use chitosan to modify curcumin, but none of them can obtain a curcumin product with strong water solubility, high stability, good flowability in harsh environment and low hygroscopicity, which cannot meet the requirements of low hygroscopicity of the product during long-term transportation in high temperature and high humidity environment. SUMMARY
[0006] To overcome the shortcomings and disadvantages of the existing technology, the primary objective of this invention is to provide a method for preparing water-soluble turmeric with low hygroscopicity and high stability. The method first involves mixing and cross-linking a chitosan acetic acid solution with a turmeric ethanol solution to obtain curcumin-chitosan complex nanoparticles. Then, using the curcumin-chitosan complex nanoparticles and a suitable wall material aqueous solution as raw materials, a combination of emulsification, homogenization, wet grinding, and spray drying techniques is employed to obtain water-soluble turmeric with low hygroscopicity and high stability.
[0007] Another objective of this invention is to provide a water-soluble turmeric with low hygroscopicity and high stability prepared by the above process. This product has a high curcumin content, good light and heat stability (curcumin content ≥10%, and light and heat stability are significantly improved compared with ordinary water-soluble turmeric), and can not clump after exposure to high temperature and high humidity (40℃, relative humidity 85%) environment for 6-8 hours. The product has good flowability and can meet the requirements of low hygroscopicity and high stability of products in international trade due to the high temperature, high humidity and long sea voyage environment.
[0008] Another object of the present invention is to provide the application of the above-mentioned water-soluble turmeric with low hygroscopicity and high stability.
[0009] The objective of this invention is achieved through the following technical solution:
[0010] A method for preparing water-soluble turmeric with low hygroscopicity and high stability includes the following steps:
[0011] (1) Dissolve curcumin in ethanol to obtain curcumin-ethanol solution; dissolve chitosan in acetic acid solution to obtain chitosan-acetic acid solution;
[0012] (2) While stirring, the curcumin-ethanol solution was slowly added to the chitosan-acetic acid solution and stirred until homogeneous. Then the pH value of the solution was adjusted to crosslink the solution. The precipitate was collected and spray-dried to obtain curcumin-chitosan complex nanoparticles.
[0013] (3) After mixing and dissolving sodium octenyl succinate starch, maltodextrin, highly branched cyclic dextrin, hydroxypropyl starch, antioxidant and water, a wall material solution is obtained. Curcumin-chitosan complex nanoparticles are added and emulsified, homogenized and wet-milled to obtain a uniform curcumin dispersion.
[0014] (4) The curcumin dispersion obtained in step (3) is spray-dried to obtain water-soluble curcumin with low hygroscopicity and high stability.
[0015] The degree of deacetylation of the chitosan mentioned in step (1) is >90%, and the viscosity is >200 mPa·s.
[0016] The concentration of ethanol mentioned in step (1) is 90~98% (v / v).
[0017] The mass ratio of the ethanol solution to curcumin in step (1) is (100:1) to (30:1).
[0018] The concentration of the acetic acid solution in step (1) is 0.5 to 5% (m / m).
[0019] The mass ratio of the acetic acid solution to chitosan in step (1) is (100:1) to (30:1).
[0020] The mass ratio of chitosan in the chitosan-acetic acid solution to curcumin in the curcumin-ethanol solution in step (2) is (0.2:1) to (1:0.2).
[0021] The pH adjusting agent for adjusting the pH of the solution in step (2) is at least one of sodium pyrophosphate, potassium dihydrogen phosphate, sodium carbonate, and sodium hexametaphosphate.
[0022] The pH in step (2) is 5.5 to 7.0.
[0023] The dissolving in step (1) or the cross-linking in step (2) can be carried out at room temperature.
[0024] The cross-linking in step (2) is carried out for 6 to 12 hours.
[0025] The spray drying method in step (2) can be centrifugal spray drying, and the conditions of the centrifugal spray drying are preferably as follows: the inlet air temperature is 160 to 200°C, the outlet air temperature is 75 to 95°C, and the bottom air temperature is 70 to 90°C.
[0026] The oxidizing agent in step (3) includes at least one of Vc, D-sodium isoascorbate, ascorbic acid palmitate, tea polyphenol, TBHQ, BHT, and BHA.
[0027] The viscosity of the 25% (m / m) aqueous solution of sodium octenyl succinate starch in step (3) is 450 to 1100 mpa.s, the DE value of the malt dextrin is less than 5, the highly branched cyclic dextrin has an average molecular weight of 380 to 420 KDa, and the hydroxypropyl starch is derived from a pre-gelatinized starch process.
[0028] The amount of the antioxidant in step (3) is 0.001% to 5% of the mass of the final product (low-hygroscopic and high-stable water-soluble curcumin).
[0029] The amount of the antioxidant in step (3) is 0.001% to 1.8% of the mass of the final product (low-hygroscopic and high-stable water-soluble curcumin).
[0030] The mass ratio of sodium octenyl succinate starch, maltodextrin, highly branched cyclodextrin and hydroxypropyl starch in step (3) is (10~35):(5~30), (5~25):(0.01~3).
[0031] The preferred mass ratio of sodium octenyl succinate starch, maltodextrin, highly branched cyclodextrin and hydroxypropyl starch in step (3) is (23~25):(10~20) or (10~16):2.
[0032] The amount of curcumin-chitosan complex nanoparticles used in step (3) is 10% to 60% of the mass of the final product (water-soluble curcumin with low hygroscopicity and high stability).
[0033] The emulsification conditions described in step (3) are: temperature of 20℃~40℃, time of 10min~60min, and emulsification speed of 3000rp.m~15000rp.m.
[0034] The homogenization conditions described in step (3) are: pressure of 30MPa to 80MPa, and homogenization times of 1 to 3 times.
[0035] The conditions for wet grinding in step (3) are: temperature of 15℃~35℃, time of 0.5~8h, and rotation speed of 500rp.m~3500rp.m.
[0036] The conditions for spray drying in step (4) are: inlet air temperature of 160℃~200℃, outlet air temperature of 70℃~100℃, and bottom air temperature of 70℃~90℃.
[0037] A water-soluble turmeric with low hygroscopicity and high stability was obtained by the above preparation method.
[0038] The water-soluble turmeric with low hygroscopicity and high stability described herein has applications in the food, pharmaceutical, or cosmetic fields.
[0039] The present invention does not impose any special restrictions on the form of the food, which can be added to liquid or solid foods, and is preferably prepared as a beverage.
[0040] If the food is a health food, the present invention does not impose any special restrictions on the dosage form of the health food, which can be a solid powder, capsule, tablet, oral liquid, etc.
[0041] Invention principle:
[0042] Curcumin is a kind of polyphenols containing diketone, which contains multiple hydroxyl groups and unsaturated double bonds in the molecular structure, and is sensitive to light, heat, oxygen, metal ions and other factors, and is easy to be oxidized and degraded. It presents a negative charge in solution. Chitosan is a product obtained by removing more than 55% of N-acetyl group from chitin, which belongs to natural degradable marine biological polysaccharides and has free amino groups, and presents a positive charge in solution. Chitosan has excellent solubility in acidic solutions such as acetic acid and citric acid, and curcumin can be dissolved in ethanol. The solutions of the two will quickly combine to form nanoparticles due to electrostatic interaction, hydrophobic interaction and hydrogen bonding force, and stable curcumin-chitosan complex nanoparticles can be obtained by drying. The combination degree of curcumin and chitosan in the complex is relatively tight, which can improve the moisture resistance of curcumin to some extent, and effectively reduce the damage of light, heat, oxygen and metal ions to curcumin, and reduce the degradation of curcumin.
[0043] The present application further uses curcumin-chitosan stable complex nanoparticles as core material, selects suitable wall material, and improves its moisture resistance, water solubility and stability through process selection:
[0044] 1. Wall material selection
[0045] (1) At a lower viscosity, the entanglement between the molecular chains of sodium octenyl succinate starch is insufficient, and it cannot stably wrap the curcumin-chitosan complex nanoparticles. At a higher viscosity, the system is too thick and heavy, which leads to uneven dispersion of the emulsion. The present application selects sodium octenyl succinate starch with a suitable viscosity range as one of the wall material raw materials, which not only maintains good emulsifying ability, but also enables the octenyl succinic acid group to be more fully exposed on the surface to play its hydrophobic role, thereby effectively preventing the entry of moisture and showing good moisture resistance.
[0046] (2) With the decrease of DE value, the glass transition temperature of maltodextrin increases, and the moisture absorption of the powder also decreases. Highly branched cyclic dextrin is a kind of cyclic dextrin with branched starch structure, which has good water solubility and the solution appears transparent. However, in the powder state, due to the branched starch structure in the outer zone, its moisture absorption is weak. Therefore, the present application selects maltodextrin with low DE value and cyclic dextrin with branches to improve the moisture resistance of curcumin-chitosan stable complex nanoparticles.
[0047] (3) Hydroxypropyl starch from pre-gelatinization process can swell in water and present a better viscous solution, but its powder state is not easy to absorb moisture and form lumps, and has good powder fluidity. Therefore, the present application selects hydroxypropyl starch from pre-gelatinization process as one of the wall material raw materials to improve the moisture resistance of curcumin-chitosan stable complex nanoparticles.
[0048] (4) The use of the antioxidant in step (3) can further improve the stability of curcumin.
[0049] 2. Process selection
[0050] After the curcumin-chitosan complex particles are mixed with the wall material composed of sodium octenyl succinate starch, malt dextrin, high-branched cyclic dextrin, hydroxypropyl starch and an antioxidant, and then subjected to a wet grinding process, the particle size can be further reduced, the solubility of the powder can be improved, the moisture resistance of curcumin can be further improved, and thus the storage stability of curcumin can be improved.
[0051] In summary, the curcumin is modified by using chitosan, sodium octenyl succinate starch, malt dextrin, high-branched cyclic dextrin, hydroxypropyl starch and the like as raw materials, and then combined with emulsification, homogenization and wet grinding technologies to obtain a curcumin emulsion with good water solubility. Finally, spray drying is adopted to obtain a curcumin powder product with good stability and water solubility. The product has low moisture absorption after long-term exposure in a high-temperature and high-humidity environment, and can maintain good powder flowability. The product meets the requirements of low moisture absorption and high stability of the product in the high-temperature, high-humidity and long-haul marine environment during international trade.
[0052] The present application has the following advantages and effects compared with the prior art:
[0053] (1) Compared with the prior art, the raw materials used in the present application are all food raw materials or antioxidants and processing aids that are safe for use in food according to GB 2760-2024. The product has higher safety, the production process uses pure physical technology, the control is stronger, the cost is lower, and it is conducive to the industrialization of the product.
[0054] (2) The present application first uses the principles of charge neutralization and hydrogen bonding to prepare high-stability curcumin-chitosan complex nanoparticles, so that curcumin and chitosan have good stable combination. The protective effect of chitosan reduces the influence of light, heat, oxygen and metal ions on curcumin, improves the stability of curcumin, and improves the dispersion effect of curcumin in the wall material solution and the moisture resistance.
[0055] (3) In the preparation process, the present application optimizes the use of raw materials with good water solubility and low moisture absorption as wall materials, optimizes the combination of emulsification, homogenization and wet grinding technologies, and obtains a curcumin product with good water solubility and stability through spray drying technology. The product powder has low moisture absorption after long-term exposure in a high-temperature and high-humidity environment, and can maintain good powder flowability, thereby solving the problem of low moisture absorption and high stability of the product in the high-temperature, high-humidity and long-haul marine environment during international trade.
[0056] (4) The prepared low-hygroscopicity and high-stability water-soluble turmeric powder product has a high content of curcumin, which can be up to 20.1%, and the product has good water solubility, good powder fluidity after being exposed to an environment of 40 DEG C and 85% relative humidity for 6-8 hours, and obviously improved stability, and can meet the application requirements in the fields of food, health food, medicine, cosmetics and the like. BRIEF DESCRIPTION OF DRAWINGS
[0057] Figure 1 is a solubility test chart of a 0.2% solution of the water-soluble turmeric powder product prepared in Examples 1-4.
[0058] Figure 2 is a solubility test chart of a 0.2% solution of the turmeric powder product prepared in Comparative Examples 1-5.
[0059] Figure 3 is a 7d light stability test chart of an aqueous solution (Abs=1.000) prepared by using the water-soluble turmeric powder product prepared in Examples 1-4.
[0060] Figure 4 is a 7d light stability test chart of an aqueous solution (Abs=1.000) prepared by using the turmeric powder product prepared in Comparative Examples 1-5.
[0061] Figure 5 is a hygroscopicity test chart of the water-soluble turmeric powder product prepared in Examples 1-4.
[0062] Figure 6 is a hygroscopicity test chart of the turmeric powder product prepared in Comparative Examples 1-5.
[0063] Figure 7 is a solubility display chart of a 0.2% solution of raw curcumin. DETAILED DESCRIPTION
[0064] The application will be further described in conjunction with the examples and the drawings, but the embodiments of the application are not limited thereto.
[0065] Unless specifically indicated otherwise, the technical means used in the examples are conventional means well known to those skilled in the art. Unless specifically indicated otherwise, the reagents, methods and equipment used in the application are conventional reagents, methods and equipment in the technical field.
[0066] In the present example, curcumin is commercially available, and the curcumin content is 95.3%, and the solubility effect thereof in water is shown in Figure 7 .
[0067] Chitosan was purchased from Jiangsu Kangting Biological Technology Co., Ltd. Maltodextrin (DE value 2.6) was purchased from Roquette (China) Co., Ltd. Maltodextrin (DE value 16.8) was purchased from Hebei Jinfeng Starch Sugar Alcohol Co., Ltd. Hydroxypropyl starch (pre-gelatinized starch process source) was purchased from Suzhou Gao Feng Starch Technology Co., Ltd. Cyclodextrin (average molecular weight 150 KDa) was purchased from Qufu Tianli Pharmaceutical Auxiliary Co., Ltd. High-branched cyclodextrin (average molecular weight 400 KDa) was purchased from Dachang Huajia Chemical International Trade (Shanghai) Co., Ltd. Sodium octenyl succinate starch (25% aqueous solution viscosity 780 mpa.s) and sodium octenyl succinate starch (25% aqueous solution viscosity 390 mpa.s) were purchased from Yiruiyan Trade (Shanghai) Co., Ltd.
[0068] Example 1
[0069] (1) Accurately weigh curcumin 20 g, dissolve in 1000 g of 95% (v / v) edible ethanol to obtain curcumin-ethanol solution; weigh 20 g of chitosan (degree of deacetylation > 90%, viscosity > 200 mpa.s) and dissolve in 1000 g of 1% (m / m) glacial acetic acid solution to obtain chitosan-acetic acid solution.
[0070] (2) Under stirring, slowly add the curcumin-ethanol solution to the chitosan-acetic acid solution, continue stirring for 60 min, then add 10% (m / m) sodium carbonate solution dropwise, adjust the pH of the solution to 6.3, stand for 8 h, discard the supernatant, collect the lower precipitate for centrifugal spray drying, the specific operation is: the inlet air temperature is 170~175℃, the outlet air temperature is 90~95℃, the bottom air temperature is 85~90℃, to obtain chitosan-curcumin complex nanoparticle powder 33.6 g.
[0071] (3) Accurately weigh sodium octenyl succinate starch (25% aqueous solution viscosity 780 mpa.s) 23 g, maltodextrin (DE value 2.6) 18 g, high-branched cyclodextrin (average molecular weight 400 KDa) 16 g, hydroxypropyl starch (pre-gelatinized process) 2 g, Vc 0.5 g, D-sodium isoascorbic acid 0.5 g, add 340 g of deionized water, stir until completely dissolved into a uniform liquid to obtain a complex wall material solution.
[0072] (4) Accurately weigh 31 g of the prepared chitosan-curcumin complex nanoparticle powder in step (2) and add it to the prepared complex wall material solution in step (3). Emulsify for 30 min at a speed of 12,000 rpm under the condition that the temperature of the material liquid is maintained at 25-35°C by using a high-speed shearing emulsifier. Homogenize the emulsified liquid for 2 times by 50 MPa, and then perform wet grinding. Specifically, the temperature of the material liquid is maintained at 25-30°C, and the grinding is performed for 6 h at a speed of 2,000 rpm by using a grinder. After the wet grinding, a uniform curcumin dispersion is obtained.
[0073] (5) Perform centrifugal spray drying on the ground curcumin dispersion. Specifically, the inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C. A low-hygroscopic and high-stable water-soluble curcumin powder product is obtained.
[0074] Example 2
[0075] (1) Accurately weigh 20 g of curcumin and dissolve it in 1,000 g of 95% (v / v) edible ethanol to obtain a curcumin-ethanol solution. Weigh 20 g of chitosan (degree of deacetylation > 90%, viscosity > 200 mpa.s) and dissolve it in 1,000 g of 1% (m / m) glacial acetic acid solution to obtain a chitosan-acetic acid solution.
[0076] (2) Slowly add the curcumin-ethanol solution to the chitosan-acetic acid solution under stirring, continuously stir for 60 min, then add 10% (m / m) sodium carbonate solution dropwise, adjust the pH value of the material liquid to 6.5, stand for 8 h, discard the supernatant, collect the precipitate at the bottom, and perform centrifugal spray drying. Specifically, the inlet air temperature is 170-175°C, the outlet air temperature is 90-95°C, and the bottom air temperature is 85-90°C. 34.3 g of chitosan-curcumin complex nanoparticle powder is obtained.
[0077] (3) Accurately weigh 23 g of sodium octenyl succinate starch (viscosity of 25% aqueous solution is 780 mpa.s), 18 g of maltodextrin (DE value is 2.6), 16 g of high-branched cyclic dextrin (average molecular weight is 400 KDa), 2 g of hydroxypropyl starch (pre-gelatinization process), 0.5 g of Vc, and 0.5 g of ascorbyl palmitate, and add 340 g of deionized water. Stir until the liquid is completely dissolved and uniform to obtain a complex wall material solution.
[0078] (4) Accurately weigh 31 g of the prepared chitosan-curcumin complex nanoparticle powder in step (2) and add it to the prepared complex wall material solution in step (3). Emulsify for 40 min at a speed of 13,000 rpm under the condition that the temperature of the material liquid is maintained at 25-35°C by using a high-speed shearing emulsifier. Homogenize the emulsified liquid for 3 times by using a 50 MPa homogenizer. Then, wet grinding is performed by using a grinder at a speed of 2,500 rpm under the condition that the temperature of the material liquid is maintained at 25-30°C for 5 h. Thus, a uniform curcumin dispersion is obtained.
[0079] (5) The ground curcumin dispersion is subjected to centrifugal spray drying. The inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C. Thus, a water-soluble curcumin powder product with low moisture absorption and high stability is obtained.
[0080] Example 3
[0081] (1) Accurately weigh 20 g of curcumin and dissolve it in 1,000 g of 95% (v / v) edible ethanol to obtain a curcumin-ethanol solution. Accurately weigh 20 g of chitosan (degree of deacetylation > 90%, viscosity > 200 mpa.s) and dissolve it in 1,000 g of 1% (m / m) glacial acetic acid solution to obtain a chitosan-acetic acid solution.
[0082] (2) Under stirring, slowly add the curcumin-ethanol solution to the chitosan-acetic acid solution. After continuous stirring for 60 min, add 10% (m / m) sodium carbonate solution dropwise to adjust the pH value of the material liquid to 6.3. After standing for 8 h, discard the supernatant and collect the precipitate at the bottom for centrifugal spray drying. The inlet air temperature is 170-175°C, the outlet air temperature is 90-95°C, and the bottom air temperature is 85-90°C. Thus, 33.2 g of chitosan-curcumin complex nanoparticle powder is obtained.
[0083] (3) Accurately weigh 25 g of sodium octenyl succinate starch (25% aqueous solution viscosity is 780 mpa.s), 20 g of maltodextrin (DE value is 2.6), 12 g of high-branched cyclic dextrin (average molecular weight is 400 KDa), 2 g of hydroxypropyl starch (pre-gelatinization process), 0.5 g of Vc, 0.5 g of sodium D-erythorbate, and 0.5 g of TBHQ. Add 340 g of deionized water and stir until a uniform liquid is obtained. Thus, a complex wall material solution is obtained.
[0084] (4) Accurately weigh 31 g of the prepared chitosan-curcumin complex nanoparticle powder in step (2) and add it to the prepared complex wall material solution in step (3). Emulsify for 30 min at a speed of 12,000 rpm under the condition that the temperature of the material liquid is maintained at 25-35°C by using a high-speed shearing emulsifier. Homogenize the emulsified liquid for 2 times by 50 MPa, and then perform wet grinding. The specific operation is as follows: maintain the temperature of the material liquid at 25-30°C, and grind for 6 h at a speed of 2,000 rpm by using a grinder. After wet grinding, a uniform curcumin dispersion is obtained.
[0085] (5) Perform centrifugal spray drying on the ground curcumin dispersion. The specific operation is as follows: the inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C. A low-hygroscopic and high-stable water-soluble curcumin powder product is obtained.
[0086] Example 4
[0087] (1) Accurately weigh 22 g of curcumin and dissolve it in 1,200 g of 95% (v / v) edible ethanol to obtain a curcumin-ethanol solution. Weigh 20 g of chitosan (degree of deacetylation > 90%, viscosity > 200 mpa.s) and dissolve it in 1,000 g of 1% (m / m) glacial acetic acid solution to obtain a chitosan-acetic acid solution.
[0088] (2) Slowly add the curcumin-ethanol solution to the chitosan-acetic acid solution under stirring, continuously stir for 60 min, then add 10% (m / m) sodium carbonate solution dropwise, adjust the pH value of the material liquid to 6.5, stand for 8 h, discard the supernatant, collect the precipitate at the bottom, and perform centrifugal spray drying. The specific operation is as follows: the inlet air temperature is 170-175°C, the outlet air temperature is 90-95°C, and the bottom air temperature is 85-90°C. 37.7 g of chitosan-curcumin complex nanoparticle powder is obtained.
[0089] (3) Accurately weigh 23 g of sodium octenyl succinate starch (viscosity of 25% aqueous solution is 780 mpa.s), 10 g of maltodextrin (DE value is 2.6), 10 g of high-branched cyclic dextrin (average molecular weight is 400 KDa), 2 g of hydroxypropyl starch (pre-gelatinization process), 0.5 g of Vc, 0.5 g of sodium D-erythorbate, 0.5 g of tea polyphenol, and add 340 g of deionized water. Stir until a uniform liquid is obtained to obtain a complex wall material solution.
[0090] (4) Accurately take 35 g of the prepared chitosan-curcumin complex nanoparticle powder in step (2) and add to the prepared complex wall material solution in step (3). Emulsify for 30 min at a speed of 12,000 rpm by using a high-speed shearing emulsifier, with the temperature of the liquid maintained at 25-35°C. Homogenize the uniformly emulsified emulsion for 2 times by using a 50 MPa homogenizer, and then perform wet grinding. The specific operation is as follows: maintain the temperature of the liquid at 25-30°C, and grind for 6 h by using a grinder at a speed of 2,000 rpm. After wet grinding, a uniform curcumin dispersion is obtained.
[0091] (5) Perform centrifugal spray drying on the ground curcumin dispersion. The specific operation is as follows: the inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C. A low-hygroscopic and high-stable water-soluble curcumin powder product is obtained.
[0092] Comparative Example 1: Without chitosan embedding
[0093] (1) Accurately take 23 g of sodium octenyl succinate starch (25% aqueous solution viscosity is 780 mpa.s), 18 g of maltodextrin (DE value is 2.6), 16 g of high-branched cyclic dextrin (average molecular weight is 400 KDa), 2 g of hydroxypropyl starch (pre-gelatinization process), 0.5 g of Vc, and 0.5 g of sodium D-erythorbate, and add 340 g of deionized water. Stir until completely dissolved into a uniform liquid to obtain a complex wall material solution.
[0094] (2) Accurately take 9.48 g of curcumin and add to the prepared complex wall material solution in step (1). Emulsify for 30 min at a speed of 12,000 rpm by using a high-speed shearing emulsifier, with the temperature of the liquid maintained at 25-35°C. Homogenize the uniformly emulsified emulsion for 2 times by using a 50 MPa homogenizer, and then perform wet grinding. The specific operation is as follows: maintain the temperature of the liquid at 25-30°C, and grind for 6 h by using a grinder at a speed of 2,000 rpm. After wet grinding, a curcumin dispersion is obtained.
[0095] (3) Perform centrifugal spray drying on the ground curcumin dispersion. The specific operation is as follows: the inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C. A curcumin powder product is obtained.
[0096] Comparative Example 2: Without grinding, homogenized for 2 times, and poor water solubility
[0097] (1) The same as in Example 1.
[0098] (2) The same as in Example 1.
[0099] (3) The same as in Example 1.
[0100] (4) The difference from Example 1 is that wet milling is not performed in this example.
[0101] (5) The homogenized curcumin dispersion liquid is subjected to spray drying, and the specific operation is as follows: the inlet air temperature is 180-185°C, the outlet air temperature is 85-90°C, and the bottom air temperature is 80-85°C, to obtain curcumin powder product.
[0102] Comparative Example 3 High-branched cyclic dextrin (average molecular weight 400 KDa) is replaced by common cyclic dextrin (average molecular weight 150 KDa)
[0103] (1) The same as Example 2.
[0104] (2) The same as Example 2.
[0105] (3) The difference from Example 2 is that the average molecular weight of the cyclic dextrin used in this example is 150 KDa.
[0106] (4) The same as Example 2.
[0107] (5) The same as Example 2.
[0108] Comparative Example 4 Starch viscosity 380-400, high hygroscopicity
[0109] (1) The same as Example 3.
[0110] (2) The same as Example 3.
[0111] (3) The difference from Example 3 is that the viscosity of the sodium octenyl succinate starch 25% aqueous solution used in this example is 380-400 mpa.s.
[0112] (4) The same as Example 3.
[0113] (5) The same as Example 3.
[0114] Comparative Example 5 Malt dextrin DE value 16-20, high hygroscopicity
[0115] (1) The same as Example 4.
[0116] (2) The same as Example 4.
[0117] (3) The difference from Example 4 is that the DE value of the malt dextrin used in this example is 16-20.
[0118] (4) The same as Example 4.
[0119] (5) The same as Example 4.
[0120] Effect Example
[0121] 1. Effect evaluation method
[0122] (1) Measurement of solubility
[0123] The samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were sequentially numbered, and each 0.2 g was taken, a small amount of distilled water (i.e. neutral aqueous solution) was added and stirred, after dissolution, distilled water was supplemented to 100 g, after stirring, centrifugation was performed at a speed of 10,000 r / min for 10 min, and after centrifugation, whether there was a precipitate deposition was judged to determine the solubility.
[0124] (2) Measurement of particle size
[0125] The 95.3% curcumin raw material and the samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were sequentially numbered, and each 1 g was taken, a small amount of distilled water was added and stirred, and the particle size was measured using a laser diffraction particle size analyzer, and D90 was recorded.
[0126] (3) Measurement of light stability
[0127] The samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were sequentially numbered, and each 0.2 g was taken, a small amount of distilled water (i.e. neutral aqueous solution) was added and stirred, after dissolution, the Abs = 1.000 of the solution was adjusted at λmax=425, after stirring, 30 mL of each was poured into a plastic bottle, and placed in a light box (temperature 37℃, light intensity: 22000LUX), and by observing the discoloration change under the same time condition, the color stability under light condition was judged.
[0128] (4) Measurement of hygroscopicity
[0129] The 95.3% curcumin raw material and the samples prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were sequentially numbered, and each 5.0 g of sample was taken, laid on a white A4 paper, and placed in an environment of 40℃ and 85% relative humidity for 6h. The moisture content before and after hygroscopicity was measured, and the increase in moisture content was calculated as the moisture content after hygroscopicity minus the moisture content before hygroscopicity.
[0130] 2. Evaluation results
[0131] (1) Solubility stability
[0132] Figure 1 The dissolution effect of Examples 1 to 4 in neutral aqueous solution is shown in the figure. Compared with the raw material 95.3% curcumin, the light transmittance of Examples 1 to 4 increased successively, and no stratification or precipitation occurred after standing, indicating that the water solubility was good. Figure 2 The dissolution effect of the water-soluble curcumin prepared in Comparative Examples 1 to 5 in aqueous solution is shown in the figure. Although Comparative Example 2 did not show stratification or precipitation after standing, the solution showed turbidity.
[0133] (2) Particle size distribution
[0134] The particle size (D90) of the water-soluble turmeric powder products prepared in Examples 1-4 was about 318-389 nm, and the particle size distribution was uniform, while the particle size of the turmeric powder product prepared in Comparative Example 2 was significantly larger than that of Examples 1-4. Among them, Comparative Example 2 did not undergo wet grinding, so its particle size was larger.
[0135] (3) Light stability
[0136] Figure 3 and Figure 4 The light color stability results of the water-soluble turmeric powders prepared in Examples 1-4 and Comparative Examples 1-5 are shown in the figure. As can be seen from the figure, the color of the water-soluble turmeric powder prepared in Examples 1-4 remained the same as the initial after 6 days of light, and there was no obvious fading phenomenon.
[0137] Comparative Example 1 did not use chitosan to embed curcumin, and the water-soluble turmeric powder product prepared therein showed obvious fading after 3 days of light. The reason is that the conventional technology is not enough to effectively embed curcumin, while the molecular chain of chitosan can wrap around the surface of curcumin particles to form a dense film, which can effectively block and scatter light, reduce the contact area of curcumin molecules with oxygen and light, and thus improve the light stability of curcumin.
[0138] Comparative Example 2 did not undergo wet grinding, and the water-soluble turmeric powder product prepared therein showed obvious fading after 4 days of light, indicating that appropriate wet grinding technology can help the wall material to further microencapsulate chitosan-curcumin composite nanoparticles, thereby improving the light stability of curcumin.
[0139] The water-soluble turmeric powder products prepared in Comparative Examples 3-5 showed slight fading after 5 days of light. Among them, Comparative Example 3 used low molecular weight cyclic dextrin, Comparative Example 4 used low viscosity sodium octenyl succinate starch, and Comparative Example 5 used high DE value malt dextrin. These raw materials can cause the final product to have high hygroscopicity, which will affect the light stability to some extent.
[0140] (4) Water increase
[0141] From Figure 5 and Figure 6 Comparing the above, after 6 hours of exposure in a humidity of 85% and a temperature of 40°C, the powders prepared in Examples 1-4 still retained good powder flowability compared to the raw material 95.3% curcumin, while the powders prepared in Comparative Examples 1 and 3-5 all showed obvious moisture absorption, indicating that embedding curcumin with chitosan, using high molecular weight high-branched cyclic dextrin, high viscosity sodium octenyl succinate starch, and low DE value malt dextrin can all improve the moisture absorption of curcumin.
[0142] Table 1. Curcumin, sample performance difference and effect statistics of examples and comparative examples
[0143]
[0144] Note: + number represents the degree. + indicates low solubility, unstable color under light conditions. +++++ indicates high solubility, stable color under light conditions.
[0145] The above examples are the preferred embodiments of the present application, but the embodiments of the present application are not limited to the above examples, and any changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principles of the present application should be equivalent replacement methods, and are included in the protection scope of the present application.
Claims
1. A method for preparing water-soluble turmeric with low hygroscopicity and high stability, characterized in that... Includes the following steps: (1) Dissolve curcumin in ethanol to obtain curcumin-ethanol solution; dissolve chitosan in acetic acid solution to obtain chitosan-acetic acid solution; (2) While stirring, the curcumin-ethanol solution was slowly added to the chitosan-acetic acid solution and stirred until homogeneous. Then the pH value of the solution was adjusted to crosslink the solution. The precipitate was collected and spray-dried to obtain curcumin-chitosan complex nanoparticles. (3) After mixing and dissolving sodium octenyl succinate starch, maltodextrin, highly branched cyclic dextrin, hydroxypropyl starch, antioxidant and water, a wall material solution is obtained. Curcumin-chitosan complex nanoparticles are added and emulsified, homogenized and wet-milled to obtain a uniform curcumin dispersion. (4) The curcumin dispersion obtained in step (3) is spray-dried to obtain water-soluble curcumin with low hygroscopicity and high stability.
2. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The degree of deacetylation of the chitosan mentioned in step (1) is >90%, and the viscosity is >200 mPa·s.
3. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The mass ratio of chitosan in the chitosan-acetic acid solution to curcumin in the curcumin-ethanol solution in step (2) is (0.2:1) to (1:0.2).
4. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The oxidant mentioned in step (3) is at least one of Vc, sodium D-isoascorbate, ascorbate palmitate, tea polyphenols, TBHQ, BHT and BHA.
5. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The viscosity of the 25% aqueous solution of sodium octenyl succinate starch in step (3) is 450~1100 mpa.s, the DE value of maltodextrin is less than 5, the average molecular weight of the highly branched cyclic dextrin is 380 kDa~420 kDa, and the hydroxypropyl starch is the source of the pregelatinized starch process.
6. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The amount of antioxidant used in step (3) is 0.001% to 5% of the mass of the water-soluble turmeric with low hygroscopicity and high stability in the final product.
7. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The mass ratio of sodium octenyl succinate starch, maltodextrin, highly branched cyclodextrin and hydroxypropyl starch in step (3) is (10~35):(5~30), (5~25):(0.01~3).
8. The method for preparing water-soluble turmeric with low hygroscopicity and high stability according to claim 1, characterized in that: The amount of curcumin-chitosan complex nanoparticles used in step (3) is 10% to 60% of the mass of the water-soluble curcumin with low hygroscopicity and high stability in the final product.
9. A water-soluble turmeric with low hygroscopicity and high stability, characterized in that... It is obtained by the preparation method according to any one of claims 1 to 8.
10. The use of the water-soluble turmeric with low hygroscopicity and high stability as described in claim 9 in the fields of food, medicine or cosmetics.
Citation Information
Patent Citations
Nanoparticles based on chitosan-lecithin loaded curcumin and preparation method thereof
CN117752615A
Adsorbent with anti-oxidation and moisture absorption effects and preparation method thereof
CN120242972A